Kidney Transplantation from Donor with SARS-CoV-2 Positivity in Brazil - Carvalho Silva, Clara Danielly Campos de; Mourão Pantoja, Geovanna; da Cruz Migone, Silvia Regina; de Paiva Rego, Viviane; de Sousa Monteiro, Ana Paula (Brazilian Journal of Transplantation, 2022)
Due to uncertainties about the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the donation of organs from individuals with suspected or confirmed infection of coronavirus disease 2019 (COVID-19) is absolute contraindication. However, this action caused reduction in the number of kidney transplants and increase inmortality in the waitlist. Because of that, the possibility of extrapulmonaryorgan transplantation from donors with SARS-CoV 2 positive with asymptomatic or mild illness has been questioned. In this context, the present study aimed to report the case of a 40-year-old female recipient in hemodialysis six years ago, whom received a kidney from donor who had real-time polymerase chain reaction (RT-PCR) test detectable for SARS CoV-2 after two days of the surgery transplantation. During hospitalization, she had no respiratory symptoms, and all RT-PCR tests for SARS-CoV-2 nasopharyngeal secretion performed had undetectable results. Thus, after 39 days of hospitalization and with good clinical and laboratory evolution, the patient was discharged toremain in outpatient follow-up.